Niosomal Doxycycline and Triamcinolone: A Novel Approach to Minimize Cytotoxicity in Endodontic Medicaments - Fereidooni , Rahim; Shahravan , Arash; Manochehrifar, Hamed; Pardakhty, Abbas; Nosrati, Fatemeh; Mollaie, Hamid Reza (Iranian Endodontic Journal, 2024)
Introduction: Mechanical root canal preparations and irrigation solutions are essential for reducing microbial counts in the root canal system. However, these methods do not completely eliminate microorganisms. Intracanal medicaments are used to further decrease microbial counts. This study aims to assess the cytotoxicity of various intracanal medicaments. Materials and methods: In this in vitro study, murine fibroblast cell lines (L929) were cultured in a controlled environment. The MTT assay was employed to evaluate the cytotoxicity of different medicament combinations, including calcium hydroxide and triamcinolone (D1), niosomal doxycycline and triamcinolone (D2), calcium hydroxide (D3), and a combination of doxycycline and triamcinolone (D4). Statistical analysis was performed using ANOVA and Dunnett’s test. Results: The results indicated that D1 and D2 had lower cytotoxicity, while D4 exhibited the highest cytotoxicity. D1 was found to be non-cytotoxic up to a concentration of 500 µg/mL over a period of 72 hours. D2 and D3 showed similar effects up to concentrations of 250 µg/mL and 100 µg/mL, respectively, for 72 hours. In contrast, D4 exhibited cytotoxicity at concentrations above 75 µg/mL at 72 hours. Conclusion: This study suggests that encapsulating doxycycline in niosomal structures (D2) reduces cytotoxicity in murine fibroblast cell lines (L929) for at least 24 and 48 hours. These findings offer promising implications for the development of endodontic medicaments with improved biocompatibility.